La producción social del riesgo en El Salvador: régimen autoritario y reestructuración municipal - Lovo Domínguez, Maya Camila (2024)
El Salvador is a territory exposed to multiple hazards and with serious levels of vulnerability. It is also a country with a nascent democracy, which since 2019 has been swept up in the wave of authoritarianism with the presidential election of Nayib Bukele. Bukele presented himself as young, anti-corruption leader, and with innovative ideas to address the challenges facing the country. For the population, he represented the possibility of a project that would fulfill its promises and respond to the needs of more than 6 million people. The figure consolidated and, despite initial criticism about his lack of grassroots organizing, he managed to mobilize and sustain support within El Salvador. He responded to popular demands regarding the ongoing security crisis by implementing an iron-fist policy: the state of exception. This mechanism, which cancels constitutional guarantees and has imprisoned thousands of people, responds to a state mobilization understood within the crisis of the capitalist system and embodied in an authoritarian neoliberal regime. The thesis argues that the neoliberal authoritarian State sustains pre-existing hazards, fuels them, and creates new ones, operating as a catalyst of risk production. Using a critical theoretical framework, within which metabolic rift, the production of space and risk, and authoritarian shifts intersect, accompanied by a qualitative methodology, the thesis analyze two main mechanisms: the creation of new anthropogenic hazards, which undermine the capacity for prevention, increase vulnerability, and reconfigure exposure by dispossession; and the municipal restructuring, implemented in 2024, as a decision that centralizes power and weakens community ties. The findings reveal the relationship between the authoritarian project and the production of risk. They also offer insights into the dangers of this shift and its popularity within the context of the climate crisis.